Internet Use, Social Networks, and Loneliness Among the Older Population in China - Tang, Dan; Jin, Yongai; Zhang, Kun; Wang, Dahua (Frontiers in Psychology, 2022)
While the rate of internet use among the older population in China is rapidly increasing, the outcomes associated with internet use remain largely unexplored. Currently, there are contradictory findings indicating that internet use is both positively and negatively associated with older adults’ subjective well-being. Thus, we examined the associations between different types of internet use, social networks, and loneliness among Chinese older adults using data from the Chinese Longitudinal Ageing Society Survey (CLASS, n=2086). Internet use was classified as interpersonal communication and information acquisition and social networks were divided into family and friendship ties. The results showed that both interpersonal communication and information acquisition were associated with lower loneliness. Interpersonal communication can increase social networks, and family ties have a mediating effect on the association between internet use for interpersonal communication and loneliness. Although information acquisition can directly decrease loneliness in older adults, it can also damage existing social networks and further increase loneliness. Family ties act as a suppressor in the association between internet use for information acquisition and loneliness. Our study further discussed important implications for improving the subjective well-being of older adults in the digital era based on the empirical findings.